Issues of legal regulation of land servitudes in the republic of kazakhstan and foreign states (Journal of actual problems of jurisprudence, 2021)
The work describes stratification of a land servitude as a branch of civil and land law and as a part of regulation over exercise of real rights. The work identifies historical, ancestral and structural features of servitudes functioning with the goal to improve relations emerging in private-legal and public-formation areas. We have determined that servitudes on land resources are not only participants in relations, which are presented in the form of civil legal relations but also is a regulator of a general civil idea about the usage of owner’s property including the necessary factors. The relevancy of the research is based on the fact that for the first time land servitudes are examined not as a category of land law, whose source is the branch of civil law, but as a doctrinal system of legal competence from civil circulation. The article shows how the status of land changes when transferred from the branch of property transaction laws to its doctrinal understanding in the form of modernising branch principles of law. Practical application of this aspect of the issue is possible under the condition of its functioning in countries that apply the servitude for purposes of structural functioning and development of the general legal system. Key words: servitude, system of real rights, civil legislation, regulation, land law.